Enzymatic reaction of β- N-methylaminoalanine with l-amino acid oxidase - Hashmi, Mazzaz; Anders, M.W. (Biochimica et biophysica acta, 1991)
The reaction of β- N-methylaminoalanine (BMAA) with l-amino acid oxidase ( l-AAO) in the presence of catalase yields ammonia and β- N-methylaminopyruvate, which was trapped as its 2,4-dinitrophenylhydrazone, as products. Incubation of BMAA with l-AAO in the presence of semicarbazide led to the formation of a semicarbazone, indicating intermediate iminium ion formation; when potassium cyanide (5 mM) was added, semicarbazone formation was blocked. The formation of β- N-methylaminopyruvate was decreased by omission of catalase and was reduced in the presence of hydrogen peroxide (100 mM). These results indicate that BMAA is converted by l-AAO to the corresponding α-imino acid, which undergoes hydrolysis to β- N-methylaminopyruvate. The α-keto acid is readily oxidized to N-methyllycine by hydrogen peroxide.